An extension and evaluation of job characteristics, organizational commitment and job satisfaction in an expatriate, guest worker, sales setting - (:unkn) unknown (My University, 2002)
Within the literature of sales management, researchers have explored different configurations of job characteristics, organizational commitment and job satisfaction. In this paper, we offer a new configuration that includes interactive effects of job characteristics and organizational commitment on job satisfaction. Utilizing structural equation modeling, we test our proposed model against three alternative models among expatriate, guest worker, salespeople in Saudi Arabia. The proposed model produces the best fit. The theoretical and managerial implications are discussed. © 2002 PSE National Educational Foundation. All rights reserved.